The Panarion of Epiphanius of Salamis. - Epiphanius, Saint, Bishop of Constantia in Cyprus, approximately 310-403. (Nag Hammadi and Manichaean Studies, 2012)
In 376 Epiphanius, chief bishop of Cyprus, published, in three Books, an historical encyclopedia of heretical sects, with the arguments, chiefly scriptural, needed to counter them, and called it the Panarion (Medicine Chest). This volume, Books II and III of the Panarion , is chiefly concerned with the sects contemporary with him, the Arian, Manichaean and others. It thus describes the thought of the fourth century church, and includes a number of source documents, many of them found only here. This is the only full translation of Epiphanius in a modern language.